THE IMPACT OF NEW TECHNOLOGIES ON ACHIEVING SUSTAINABLE INDUSTRIAL DEVELOPMENT - Kulinich, Tetiana (European Science, 2025)
The study demonstrates that the implementation of new technologies ensures a combination of economic efficiency and environmental safety, which determines their strategic importance for achieving the Sustainable Development Goals. It is shown that such te